Facts and Misconceptions about 2D:4D, Social and Risk Preferences - Alonso, Judit; Di Paolo, Roberto; Ponti, Giovanni; Sartarelli, Marcello (Frontiers in Behavioral Neuroscience, 2018)
We study how the ratio between the length of the second and fourth digit (2D:4D) correlates with choices in social and risk preferences elicitation tasks by building a large dataset from five experimental projects with more than 800 subjects. Our results confirm the recent literature that downplays the link between 2D:4D and many domains of economic interest, such as social and risk preferences. As for the former, we find that social preferences are significantly lower when 2D:4D is above the median value only for subjects with low cognitive ability. As for the latter, we find that a high 2D:4D is not correlated with the frequency of subjects' risky choices.